2011
DOI: 10.1021/bi201055c
|View full text |Cite
|
Sign up to set email alerts
|

A Reduced-Amide Inhibitor of Pin1 Binds in a Conformation Resembling a Twisted-Amide Transition State

Abstract: The mechanism of the cell cycle regulatory peptidyl prolyl isomerase (PPIase), Pin1, was investigated using reduced-amide inhibitors designed to mimic the twisted-amide transition state. Inhibitors, R–pSer–Ψ[CH2N]–Pro–2-(indol-3-yl)-ethylamine, 1 (R = fluorenylmethoxycarbonyl, Fmoc), and 2 (R = Ac), of Pin1 were synthesized and bioassayed. Inhibitor 1 had an IC50 value of 6.3 μM, which is 4.5-fold better inhibition for Pin1 than our comparable ground state analogue, a cis-amide alkene isostere containing inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 40 publications
3
61
0
1
Order By: Relevance
“…We anticipated that the ketones would be poor inhibitors, while the reduced amides, as twisted-amide analogues, would fare better. Indeed, the reduced amide 3 is a better Pin1 inhibitor than a similarly substituted substrate analogue ( Z )-alkene isostere 5 (Figure 2) [13], [27]. Our crystal structure of reduced amide 4 bound to the Pin1 catalytic site adopted a trans -pyrrolidine conformation, supporting the twisted-amide mechanism [27].…”
Section: Introductionsupporting
confidence: 53%
“…We anticipated that the ketones would be poor inhibitors, while the reduced amides, as twisted-amide analogues, would fare better. Indeed, the reduced amide 3 is a better Pin1 inhibitor than a similarly substituted substrate analogue ( Z )-alkene isostere 5 (Figure 2) [13], [27]. Our crystal structure of reduced amide 4 bound to the Pin1 catalytic site adopted a trans -pyrrolidine conformation, supporting the twisted-amide mechanism [27].…”
Section: Introductionsupporting
confidence: 53%
“…The crystal structure of a reduced amide−Pin1 complex (PDB entry 3NTP), where the structure is considered to mimic the transition state complex with pSer-Pro, showed that the basic triad residues form hydrogen bonds to the phosphate moiety in the substrate. 19 The side chain reorientation of the basic triad in the C113D mutant may explain the severely reduced capacity for binding to the phosphorylated substrate ( Figure 1B).…”
Section: ■ Resultsmentioning
confidence: 99%
“…18 The crystal structure of Pin1 with a reduced amide inhibitor bound in the active site showed the compound structure was close to the twisted amide, which is proposed to exist in a transition state. 19 Molecular dynamics simulations gave other insights into the cis−trans isomerization process. Hamelberg and co-workers applied molecular dynamics simulations to sample the entire conformational ensemble of the Pin1 substrate complex, with the corresponding relative binding free energies, during the cis− trans conversion of the substrate.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…41, 42 In addition, the flexibility of the interactions between the phosphate group and the positive triad during the rotation permits transition-state stabilization. 36 …”
Section: Discussionmentioning
confidence: 99%